Vaccine hesitancy and the willingness to recommend the COVID-19 vaccine to children in a rural country on the United States-Mexico border - Darisi, Raghu D.; Buckland, Audrey J.; Morales, Mario; Ingram, Maia; Harris, Emily; Holzberg, Jeffrey R. (Frontiers in Public Health, 2023)
Introduction As of October 26, 2022, only 9% of children in the United States aged 6 months to 4 years have received at least one dose of COVID-19 vaccine despite FDA approval since June 17, 2022. Rates are better yet still low for children aged 5 to 11 years as nearly 30% were fully vaccinated as of August 23, 2022. Vaccine hesitancy among adults is one of the major factors affecting low vaccine uptake rates in children against COVID-19, yet most studies examining vaccine hesitancy have targeted school-age and adolescent children. Methods With the aim of assessing the willingness to recommend the COVID-19 vaccination to children under 5 years compared to children 5 to 12 years of age, a county-wide survey was conducted between January 11 and March 7, 2022, among adults on the United States-Mexico border. Results Among the 765 responses, 72.5% were female and 42.3% were Latinx. The most significant factor associated with likelihood to recommend the COVID-19 vaccine to children less than 5 years and 5–12 years of age was adult vaccination status. Ordinal logistic regression also indicated that ethnicity, primary language, being a parent, previous COVID-19 infection, and concern about getting COVID-19 in the future were significantly associated with likelihood of COVID-19 vaccine recommendation to children < 5 years and 5–12 years old. Discussion This study found high consistency among respondents in their willingness to vaccinate children aged < 5 years compared with children aged 5–12 years. Our findings support public health strategies that target adult vaccinations as an avenue to improve childhood vaccinations for young children